Optimizing sustainable cement replacement using ceramic tile waste: Enhanced strength and microstructural performance - Salisa Chaiyaput; Pimchanok Sertsoongnern; Paratee Sukkatorn; Lindung Zalbuin Mase; Jiratchaya Ayawanna (Results in Engineering, 2026)
The increasing demand for cement in the construction industry has intensified the depletion of natural resources and accelerated environmental impacts associated with cement production, including high CO 2 emissions. Simultaneously, the ceramic tile manufacturing process generates substantial amounts of waste, particularly sludge waste and rectified tile waste, which are typically discarded despite their high silica and alumina contents. This study examines the potential of utilizing ceramic tile waste as a partial replacement for cement in mortar formulations, promoting sustainable material use. XRF and XRD analyses revealed substantial SiO 2 concentrations in both waste types, indicating suitability for pozzolanic reactions. Mortar samples containing varied amounts of tile waste were examined for physical properties, compressive strength, and microstructural characteristics. The replacement of 50% of cement with rectified tile waste significantly enhanced long-term strength, surpassing that of the 100% cement control at 28 days, due to improved pozzolanic activity and a denser microstructure. Conversely, the replacement of sludge waste led to reduced strength due to higher porosity and weaker hydration. Further investigation of rectified tile waste at replacement levels of 30-70% confirmed that 50% substitution provides the optimum balance between strength performance and material sustainability. Microstructural analysis with SEM confirmed these findings, revealing well-formed C-S-H and reduced pore spaces at the optimal replacement ratio. Overall, rectified tile waste demonstrates strong potential as a sustainable cement replacement material, offering reductions in cement consumption, CO 2 emissions, and ceramic waste disposal while maintaining or improving mechanical performance.
Keywords: Concrete and Cement Materials Research; Recycling and utilization of industrial and municipal waste in materials production; Recycled Aggregate Concrete Performance